Improving the profit of Algerian banks in light of the risks of digital banking transactions in the Algerian banking sector for the period - Melikaoui, hadjila; hamadi, nabil (Journal of Research in Finance and Accounting, 2025)
The shift of Algerian banks towards electronic banking transactions is expected to achieve a positive impact on the bank's profitability, but with the need for optimal management of banking risks. With this, the study proposed a quantitative model to analyze the impact of each of the reputational risks and the strategic risks of electronic banking on the profitability of 28 public and private banks during the period 2010-2022. A positive direct significant relationship was found between reducing risks and improving profitability. Therefore, we recommended the need to work on providing requirements to reduce electronic banking risks, improve the quality and quality of electronic banking services, and adopt a clear risk management strategy